THE BLENDED LEARNING METHOD IN IMPROVING SPEAKING SKILLS OF MIDDLE SCHOOL STUDENTS - Eva Simanjorang; Joshua Simatupang; Windi Butarbutar; Koleta Purba; Sahlan Tampubolon; Febrika Dwi Lestari Lumbantoruan (STKIP PGRI Situbondo, 2023)
Implementing online learning causes a lack of enthusiasm and low motivation to learn English speaking skills. This study aims to analyze English speaking skills by implementing Hybrid learning-based in junior high school. This research used classroom action research (CAR) that determines the set of two cycles according to the characteristics of the material. Research in each Cycle was carried out through four stages. Application of the Learning Model Hybrid learning applies two activities which include bold and limited face-to-face learning. The number of students in the class was divided into odd and even absences. Data collection methods used observation, evaluation, and student responses. Methods of data analysis employed descriptive analysis. Preliminary learning outcomes before implementing hybrid learning mastery were only 54,84%. Cycle I showed an increase in learning completeness, reaching 84.2%. Cycle II also showed an increase in learning completeness with 94.7%. Data from Cycle I and Cycle II results reveal that implementing Hybrid learning can improve learning outcomes and the proportion of minimum mastery standards that is very significant. The implications of this research are expected to improve English speaking skills in class X students.